STRATEGI GURU AQIDAH AKHLAK DALAM PENANGGULANGAN POTENSI RADIKALISME DI MAN 1 KOTA SUKABUMI - Mulyawan Safwandy Nugraha; Ai Rohayani (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
This study aims to determine: (1) the factors that influence the birth of the potential for religious radicalism among Madrasah Aliyah students; (2) Akidah Moral Teacher Strategy in overcoming the potential of religious radicalism through learning in MAN 1 Sukabumi City; (3) Moral Teachers Strategy in overcoming the potential of religious radicalism through habituation and activities outside of learning in MAN 1 Sukabumi City. Data collection through in-depth interviews, observation and documentation study. Key words: Strategy; Teacher; Religious Radicalism; Madrasah Aliyah